Association of self-reported happiness with sociodemographic factors and personal habits amongst students in a university in Karachi - Hareem Syed; Amara Zafar; Maheen Khan; Alina Mohib (Journal of the Pakistan Medical Association, 2020)
Abstract The aim of this study was to determine the association of happiness with sociodemographic factors and personal habits among university students in Karachi, Pakistan. This cross-sectional study was conducted at Bahria University (BU), Karachi, from January 2012 till December 2013 on 813 students. There was a significant positive relationship between happiness and having a well-off family background (p value<0.001), having breakfast (p value=0.021), wearing a seat belt (p value=0.005) and getting regular dental check-ups (p value<0.001). We also found a significant negative association between happiness and the use of tobacco (p value=0.048), being on a weight loss diet (p value=0.048) and being married (p value=0.043).Hence, behaviours such as smoking and following unhealthy weight loss diets are proven to be associated negatively with a person’s state of happiness and should be discouraged;while healthy behaviours such as having breakfast and getting dental check-ups should be encouraged. Keywords: Happiness, behaviour, health, students